Teachers’ Practices in Blended Learning Environment: Perception of Students at Secondary Education Level - Muhammad, ASIF; Palitha Edirisingha; Ali, Riasat; Shehzad, Saqib (Journal of Education and Educational Development, 2020)
The overload in teachers’ role has been renowned and optimized by generative adaptation of technology, which means teaching capability can be improved if educationalists blend technology tropically and timely. Based on this belief, this study tried to judge the teachers’ practices in Blended Learning (BL) environment in the context of secondary level students. For this purpose, an empirical study was conducted at Government High School No.1 (boys) Tordher district Swabi Khyber Pakhtun Khwa (KPK). All 120 enrolled science students of grade 9 and 4 science teachers participated in the study. The students’ perception of teachers’ practices of preparedness, innovation, and developing feedback skills in the BL environmentwere ascertained through a survey questionnaire whereas 20 students were also interviewed randomly. The responses were measured through a 5-point based Likert scale, data were analyzed through descriptive statistics. The research method used for this study was the explanatory sequential approach of mixed-method (Creswell, 2014). Based on the study findings, teachers’ practices improved in the BL environment and hence recommended that secondary school teachers need to be encouraged to use the BL approach instead of merely using Information Communication Technology (ICT) or traditional methods of teaching.
Keywords: BL emergence; BL utilities; e-learning vs BL; teachers’ BL savvy; using educational technology